IMPLEMENTASI PENDIDIKAN KARAKTER PADA MATA PELAJARAN MATEMATIKA KELAS 4 DI SEKOLAH DASAR - Anastya Nida Alhana (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
This article examines the implementation of character education in mathematics in class 4B of SD Islam Plus Masyitoh Kroya. From the studies conducted, it can be seen that there are at least three values in character education that have been implemented in the teaching and learning process of mathematics in class 4B of SD Islam Plus Masyitoh Kroya, including (1) religious values through reading prayers before and after lessons take place; (2) the value of honesty in the process of working on questions and assignments and; (3) the value of discipline through punishment and reward methods. In instilling character in students who teach mathematics subjects, they experience several obstacles, starting from controlling students outside of school, which is very difficult even though the role of parents is not optimal. Nonetheless, good communication between tutors and student guardians continues to be pursued so that this character education can be implemented optimally